The impact of foreign portfolio flows on the perfomance of the Zimbabwe Stock Exchange (2009 – 2013) - Chihava, Anold Providence (Midlands State University, 2014)
The basic objective of this research was to assess the effect of foreign portfolio flows on the performance Zimbabwe Stock Exchange during the study period. In pursuing this major objective the study also determined the granger causality between foreign flows and returns, the behaviour patterns shown by foreign investors on the local bourse and assessed the impact that certain foreign investor behavior has on stock performance measured by stock return. The research methodology in this dissertation was based on quantitative analytics using the data collected mostly from websites of the Reserve Bank of Zimbabwe, US Federal Bank, and the Zimbabwe Stock Exchange. The study was undertaken for the reference period of approximately five years from 2009-13. The researcher also went on to analyse the data that was gathered in order to come up with viable analysis. The gathered information was analyzed using tools like, graphs and tables as a way of giving a clear view of the results that were found from the research. The key results of the study points out that participation of foreign investors has an effect on domestic stock market returns and that stock market return is mainly affected by unexpected flows and not significantly by the contemporaneous value of expected flows. The price pressure hypothesis is supported, with security prices revised by lags. The base-broadening hypothesis holds, hence, the amount of foreign investment in the market drives up returns and hence performance of the market. Macroeconomic factors, especially the change in exchange rate and risk free rate, are important in determining returns. The results suggest that though portfolio flows in lower the cost of capital and financing growth, promoting local investment and macroeconomic stability is also important in improving performance of the Zimbabwe Stock Exchange. The study concludes by making recommendations aimed at improving market capitalization and foreign investor confidence.